Corporate Scandals and Capital Structure - Bonini, Stefano (Journal of business ethics, 2010)
We analyze whether companies involved in a security class action suit (SCAS) exhibit differential capital structure decisions, and if the information revealed by a corporate scandal affects the security issuances and stock prices of industry peers. Our findings show that before a SCAS is filed, companies involved in a scandal show a greater amount of security offerings than their peers and, due to equity mispricing, are more likely to use equity as a financing mechanism. Following a SCAS filing, these companies exhibit a decreasing amount of total external finance raised and lower levels of book and market leverage. Industry peers’ issuance patterns exhibit significant contagion, with reduced debt and equity issuance following the SCAS filing. Corporate scandals also have meaningful negative effects on stock prices and bond ratings. Similar to capital structure, we document contagion at the industry level with peers’ share prices yielding negative returns as well.